2014
DOI: 10.1103/physrevb.90.094208
|View full text |Cite
|
Sign up to set email alerts
|

Study of off-diagonal disorder using the typical medium dynamical cluster approximation

Abstract: We generalize the typical medium dynamical cluster approximation (TMDCA) and the local Blackman, Esterling, and Berk (BEB) method for systems with off-diagonal disorder. Using our extended formalism we perform a systematic study of the effects of non-local disorder-induced correlations and off-diagonal disorder on the density of states and the mobility edge of the Anderson localized states. We apply our method to the three-dimensional Anderson model with configuration dependent hopping and find fast convergenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…The lack of a single method satisfying all the criteria mentioned above for phononic systems motivates us to adapt the dynamical cluster approximation (DCA) and the typical medium DCA (TMDCA) for disordered phononic systems to capture the Anderson localization of phonons since these methods have been shown to work extraordinarily well in electronic systems [58][59][60][61] . The main difficulty inhibiting the development of such a method for the study of Anderson localization of phonons lies in finding a single particle order parameter to characterize the Anderson transition in disordered phononic systems.…”
Section: Anderson Localization (Al)mentioning
confidence: 99%
“…The lack of a single method satisfying all the criteria mentioned above for phononic systems motivates us to adapt the dynamical cluster approximation (DCA) and the typical medium DCA (TMDCA) for disordered phononic systems to capture the Anderson localization of phonons since these methods have been shown to work extraordinarily well in electronic systems [58][59][60][61] . The main difficulty inhibiting the development of such a method for the study of Anderson localization of phonons lies in finding a single particle order parameter to characterize the Anderson transition in disordered phononic systems.…”
Section: Anderson Localization (Al)mentioning
confidence: 99%
“…We demonstrated that the TMDCA overcomes the shortcomings of the TMT and is able to qualitatively and quantitatively describe Anderson localization. We also extended this method to models with off-diagonal disorder 63 , multiband systems 64 , and interactions 65? .…”
Section: Introductionmentioning
confidence: 99%
“…In relevant cases, our results are found to be in excellent agreement with recent large-scale exact diagonalization results 37 , as well as with recent experiments 29 . Moreover, recently developed cluster refinements of TMT demonstrated [39][40][41] that significant corrections to (single site) TMT are only found very close to the Anderson transition. All these findings provide further evidence that TMT represents a flexible and practically useful tool for successfully describing the main qualitative trends for physical observables, in the vicinity of disorder-driven metal-insulator transitions.…”
Section: Discussionmentioning
confidence: 99%